1991
DOI: 10.1177/002221949102400210
|View full text |Cite
|
Sign up to set email alerts
|

Language Abilities and Progress in a Direct Instruction Reading Program for Students with Learning Disabilities

Abstract: Direct instruction reading programs have been found to be a successful way to teach reading to many, but not all, students with learning disabilities. This study investigated whether reading improvement for students with learning disabilities receiving reading instruction through a direct instruction reading program might be related to their language abilities. The reading progress of 26 students (19 male, 7 female), 7 to 10 years old, was measured over 2 years. In addition, phonological and syntactic abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Direct instruction is a system of teaching that has been demonstrated to be effective with a range of students (Adams & Engelmann, 1996) including those considered to be disadvantaged (Fredrick, Keel, & Neel, in press;Kaiser, Palumbo, Bialozor, & McLaughlin, 1989;Lum & Morton, 1984;Robinson & Hesse, 1981;Tarver & Jung, 1995) and those with mild disabilities (Anderson & Keel, in press;Darch, 1989;Darch & Carnine, 1986;Kelly, Gersten, & Carnine, 1990;Kuder, 1990Kuder, , 1991Lloyd, Cullinan, Heins, & Epstein, 1980). The components of direct instruction include explicit step-by-step teaching procedures that account for student mastery, immediate feedback, practice, and gradual fading from teacher direction.…”
Section: · Direct Instructionmentioning
confidence: 99%
“…Direct instruction is a system of teaching that has been demonstrated to be effective with a range of students (Adams & Engelmann, 1996) including those considered to be disadvantaged (Fredrick, Keel, & Neel, in press;Kaiser, Palumbo, Bialozor, & McLaughlin, 1989;Lum & Morton, 1984;Robinson & Hesse, 1981;Tarver & Jung, 1995) and those with mild disabilities (Anderson & Keel, in press;Darch, 1989;Darch & Carnine, 1986;Kelly, Gersten, & Carnine, 1990;Kuder, 1990Kuder, , 1991Lloyd, Cullinan, Heins, & Epstein, 1980). The components of direct instruction include explicit step-by-step teaching procedures that account for student mastery, immediate feedback, practice, and gradual fading from teacher direction.…”
Section: · Direct Instructionmentioning
confidence: 99%
“…These results have appeared with the general student population (e.g., Becker & Carnine, 1980;O'Brien & Ware, 2002;Stebbins, St. Pierre, Proper, Anderson, & Cerva, 1977;Vitale & Joseph, 2008) and with students with disabilities. Studies have demonstrated the effectiveness of DI reading programs with students with learning disabilities (Benner, 2007;Benner, Kinder, Beaudoin, Stein, & Hirschmann, 2005;Cooke, Gibbs, Campbell, & Shalvis, 2004;Kuder, 1990Kuder, , 1991Malmgren & Leone, 2000;Scarlato & Asahara, 2004), students with intellectual disabilities (Flores, Shippen, Alberto, & Crowe, 2004;Haring & Krug, 1975;Maggs & Morath, 1976;Malmgren & Leone, 2000;Riepl, Marchand-Martella, & Martella, 2008), children who demonstrate developmental delays (Flores & Ganz, 2007;Riepl et al, 2008), and students identified with emotional disturbance (Benner, 2007;Cook et al, 2004;Malmgren & Leone, 2000;Scarlato & Asahara, 2004;Strong, Wehby, Falk, & Lane, 2004). Additionally, DI reading programs have been effectively implemented outside of traditional elementary schools in a variety of settings, including middle schools (Dowdell, 1996;Grossen, 2004;Lewis, 1982;Shippen, Houchins, Steventon, & Sartor, 2005), high schools (Harris, Marchand-Martella, & Martella, 2000;Marchand-Martella, Martella, Orlob, & Ebey, 2000), a residential treatment center (Scarlato & Asahara, 2004), alternative schools (Steventon & Fredrick, 2003), and juvenile corrections facilities (Drakeford, 2002;Houchins, ...…”
Section: The Effectiveness Of Direct Instructionmentioning
confidence: 99%
“…Because TBI may lead to slower processing of information (Bawden et al., 1985) and executive function problems (Gioia et al, 2002), these children may benefit from a step‐wise incremental curriculum, delivered in a predictable format (Glang et al, 2008b). Direct instruction is an approach which provides this structure and which works for children with a range of difficulties (Humphries, Neufeld, Johnson, Engels, & McKay, 2005; Grossen, 2004; Kuder, 1991; White, 1988). A description of its use with three children following TBI (Glang, Singer, Cooley, & Tish, 1992) suggests that direct instruction can be a useful strategy with this group.…”
Section: Longer‐term Interventionsmentioning
confidence: 99%